SÍNTESE E CARACTERIZAÇÃO DE NANOCOMPÓSITOS POLIMÉRICOS COM PROPRIEDADES DE ATENUAÇÃO PARA O USO EM PROTEÇÃO RADIOLÓGICA - Cadó, Ronan Gorski (2016)
Ionizing radiations with X-rays energy range offer risk to human health and might be source of interference on sensitive devices. The increased use of ionizing radiations causes the need of development of new materials for radiological protection. The main goal of this study is to determine the attenuation properties of X-rays in polymeric nanocomposites with insertion of metal oxides. To obtain the nanocomposite, lead, cooper and tungsten oxides were synthesized. The oxides were characterized by X-ray diffraction, infrared spectroscopy and zeta potential with different pH. The synthesized oxides have average crystallite size between 25 and 55 nm. Polymeric films were made by dissolving polyamide 6.6 pellets in different combinations of formic acid / chloroform, determining by stress-strain tests that the combination 75/25 (%/%) of the reagents had better condition for the polymeric film use as fabric. The oxides were dispersed on the polymer solution for homogenization, obtaining polymer nanocomposites with 0.2 g, 0.08 g and 0.02 g of PbO, 0.2 g, 0.08 g and 0.02 g of CuO and 0.2 g of WO3.The nanocomposites were evaluated by X-ray diffraction, showing diffraction peaks in the amorphous region of the polymer film. The attenuation of X-rays was measured with the aid of an ionization chamber, varying the voltage of the X-ray tube (kV), and the time of exposure (mAs). The results showed attenuation of 26% compared to the polymeric film, in combination kV/mAs 40/10 and 13.11% in 100/10, for the nanocomposite with higher amounts of PbO. The nanocomposite with WO3 showed attenuation of 21,78% and 11,5% compared to the polymeric film, in the combinations 40/10 and 100/10, respectively. The nanocomposite of CuO with the larger amount of the oxide, showed attenuation of 10.11% and 4.5%, compared to the polymeric film, in combinations of 40/10 and 100/10, respectively. These results suggest that the nanocomposites produced has great potential for application in radiological protection.